Do organizations need 'cynics'? : what happened when Diogenes met Alexander the Great - Morrell, Kevin (London : SAGE Publications: SAGE Business Cases Originals, 2021)
This case discusses the topic of cynicism, drawing on the example of an ancient Cynic: Diogenes. The term cynic has a rich heritage because it refers to a school of ancient Greek thinkers of whom Diogenes was the most famous representative. Cynics from this school deliberately broke with conventions - sometimes in quite shocking ways - to call attention to what they saw as artificiality, hypocrisy, or empty posturing in their society. Readers are given the example of how Diogenes took the Emperor Alexander the Great down a notch or two. They are then asked to imagine whether there could be a role for this kind of puncturing of power and authority in contemporary organizations. The chances for this may be slim, since organizations put a premium on loyalty and corporate leaders do tend to take themselves seriously. However, there may be potential benefits for organizations that find ways to integrate cynics. These individuals might find it helpful to question motives, 'to blow away the fog and confusion and see reality with lucidity and clarity.' Organizations might be able to learn if they encourage a diversity of voices and perspectives - rather than employ people who simply parrot slogans to one another.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Diogenes, -- -approximately 323 B.C.; Alexander, -- the Great, -- 356 B.C.-323 B.C.; Cynicism -- Case studies; Business enterprises -- Philosophy -- Case studies; Industrial management -- Philosophy -- Case studies